PENGGUNAAN KAIDAH BAHASA INDONESIA DALAM PENULISAN SKRIPSI MAHASISWA FAKULTAS ILMU BUDAYA UNIVERSITAS BRAWIJAYA - Warsiman (Universitas Insan Budi Utomo, 2020)
The use of Indonesian rules in writing student thesis is very important, but in some cases errors are still found. The omission of errors that will continue to have a negative impact on the quality of thesis/scientific work of students, and can further reduce the authority of the institution. This is the basis of this research. The research method used is descriptive qualitative research. The results showed that the misuse of Indonesian rules usage in the thesis writing of the Faculty of Cultural Sciences, University of Brawijaya Malang was relatively high. Therefore, there needs to be an effort from the leadership to follow up these findings by paying attention to the lecturer’s competencies of Indonesian general subjects lecturer, both through increasing hours of study and providing courses for final semester students.